Relationship Power and Intimate Partner Violence in Sexual Minority Male Couples. Issue 1 (January 2022) - Bosco, Stephen C.; Robles, Gabriel; Stephenson, Rob; Starks, Tyrel J.
Objective: The objective of the present study was to test pathways implied by Disempowerment Theory to predict intimate partner violence (IPV) among men in a same-sex relationship.Background: Sexual minority men in relationships experience rates of IPV comparable with heterosexual women, yet most research on IPV focuses on heterosexual couples. Disempowerment Theory suggests that a range of individual, family-of-origin, and intimate relationship risk factors predict the use of violence to re-establish power in a relationship.Method: Data for the present study were gathered from an online survey completed by sexual minority men currently in a same-sex relationship ( n = 339). Analysis of data included two steps: (a) we tested the direct effect of individual, family, and relational predictors on the odds of IPV and (b) we calculated a path model that included relationship power as a link between the predictors (individual, family, and relational) and IPV.Results: In line with Disempowerment Theory, relationship power was negatively associated with IPV. Bivariate analysis indicated an association between childhood sexual abuse and IPV, but childhood sexual abuse was not predictive of IPV through relationship power. Other individual (depression) and relationship-specific (sexual communication and relationship satisfaction) risk factors were associated with IPV indirectly through relationship power.Conclusion: Disempowerment Theory may provide a useful framework for understanding the occurrence of IPV in sexual minority male couples. It may also provide a starting point for the development of multi-component interventions to reduce violence in these couples.